The Influence of Work-Life Balance on the Work Motivation of Millennial Employees in Makassar City - Daniel Lallo Pakiding; Brilliant Halim; Uli Urbanus Bubun (Brilliant International Journal Of Management And Tourism, 2026)
This study aims to analyze the influence of work-life balance on the work motivation of millennial employees in Makassar City. Work-life balance is an important factor that can affect employee well-being and motivation, especially for the millennial generation who have different expectations in the world of work. The research method used is quantitative with an associative approach, involving 100 millennial employee respondents who work in various companies in Makassar City. Data were collected through questionnaires and analyzed using simple linear regression. The results show that work-life balance has a positive and significant influence on the work motivation of millennial employees. Employees who have a balance between work and their personal lives tend to be more motivated and productive. In addition, a supportive work environment and flexible work policies contribute to improving employee engagement and job satisfaction. Therefore, companies in Makassar City are advised to implement policies that support work-life balance to improve employee motivation and well-being, as well as to enhance organizational performance and sustainability in the long term.